Advances in the Studies of the Benthic Zone - Soto, Luis A. (IntechOpen, 2020)
This book is an unpretentious editing venture to fill the gap in our current knowledge on the ecological implications caused by anthropogenic disturbances upon benthic communities in several regions of the world, including the Western Atlantic, the Mediterranean Sea, and the Eastern Pacific Ocean, as well as the pristine environments of the Andes in South America. The common goal of the contributing authors in this book was to unravel the complex processes that make possible the life existence of bottom-living animals in different environmental scenarios. To achieve such a goal, the authors focus their attention on the emerging issues inherent to global climate change or the pollution of aquatic systems. These are all themes that might be of interest to scientists active in a wide range of oceanographic subdisciplines. Well-established researchers would appreciate the innovative approach adopted in each chapter of the book, which extends from the ecosystem level to refined molecular interpretations.